Unraveling Indonesia's Stock Market Dynamics for Global Insights: Mengungkap Dinamika Pasar Saham Indonesia untuk Wawasan Global - Susanti, Rizki; Hanif, Aisha (Indonesian Journal of Law and Economics Review, 2024)
This study examines stock price dynamics in the LQ-45 index on the Indonesia Stock Exchange from 2017 to 2021, focusing on factors like inflation, interest rates, Earning Per Share (EPS), and Price Earning Ratio (PER). Using quantitative methods and data from annual reports and official sources, the research found that inflation and interest rates had no significant impact on stock prices, while EPS and PER showed a positive and significant influence. These findings contribute to understanding stock market behavior and can guide companies and investors in making informed decisions. Highlight: Stock Price Trends: LQ-45 index insights on market dynamics. Economic Influences: Examining inflation and interest rates' impact. EPS and PER Impact: Significant role in stock valuation revealed. Keyword: Stock Prices, LQ-45 Index, Indonesia Stock Exchange, Inflation, Earning Per Share (EPS)